Left main coronary arterial endothelial function and heterogenous segmental epicardial vasomotor reactivity in vivo: novel insights with intravascular ultrasonography. (14th July 2014) - Puri, Rishi; Nicholls, Stephen J.; Brennan, Danielle M.; Andrews, Jordan; King, Karilane L.; Liew, Gary Y.; Carbone, Angelo; Copus, Barbara; Nelson, Adam J.; Kapadia, Samir R.; Tuzcu, Emin Murat; Beltrame, John F.; et al.
Abstract: Aims: While the relationship between epicardial coronary vasomotor reactivity and cardiovascular events is well established, this observation has yet to be evaluated within the left main coronary artery (LMCA) in humans in vivo . Our aims were to test the endothelium-dependent vasomotor properties of the LMCA, and to compare these responses to downstream epicardial segments. Methods and results: Thirty patients referred for coronary angiography underwent intracoronary (IC) salbutamol provocation during intravascular ultrasound imaging within a non-critically diseased, left-sided conduit vessel. Macrovascular vasomotor response [change in average lumen area (LA) at baseline and following 5 min of 0.30 µg/min IC salbutamol] and percent atheroma volume (PAV) were evaluated in 30 LMCA, 42 proximal, 109 mid, and 132 distal epicardial coronary segments. In comparison with all other segments, the LMCA had the greatest lumen and vessel areas ( P < 0.001), yet the proximal epicardial segments contained the greatest PAV ( P < 0.02). The mid and distal epicardial segments displayed significant endothelium-dependent vasodilatation from baseline ( P = 0.017 and <0.001, respectively); however, the proximal epicardial and LMCA segments did not ( P = 0.45 and 0.16, respectively). Significant segmental vasomotor heterogeneity was noted in all 30 patients, with opposing vasomotor responses between adjacent LMCA and epicardial segments. Across all segments, baseline LA inversely correlated with the % change in LA ( r = −0.16, P = 0.0005). Conclusion: Endothelium-dependent vasomotor reactivity is heterogenous within the conduit coronary system. Vascular dynamic responses were less prominent in the larger calibre LMCA and proximal epicardial segments. This may, in part, relate to higher shear stress in smaller, distal segments and yet also may explain the propensity for culprit plaques to cluster proximally.